"It Made Me Think in a Different Way": Bilingual Students' Perspectives on Multimodal Composing in the English Language Arts Classroom. Issue 2 (9th August 2021) - Smith, Blaine E.; Amgott, Natalie; Malova, Irina
Abstract: This study examined 94 bilingual and emergent bilingual 10th grade students' perspectives on multimodal composing for academic purposes in their English Language Arts class. A social semiotics theoretical framework was employed to understand students' views of the affordances and constraints when composing three digital multimodal projects—a hypertext poetry analysis, a persuasive podcast, and a video literary analysis. Qualitative analysis of interviews and written reflections revealed how students overwhelmingly held a positive view of composing with multiple modes for academic purposes. Students detailed the unique semiotic resources of nonlinguistic modes for supporting their understanding of the content and innovative meaning‐making. A majority of students described how communicating through multiple modes offered impactful opportunities to express their bilingual/bicultural identities as well as explore the affective dimensions of the English Language Arts content. Additionally, students explained how the process of multimodal composing fostered peer collaboration and creating meaningful connections to other works and their lives. Along with affordances, students also described a variety of challenges when designing their digital projects, including technical difficulties, uncertainty of expectations, and sufficiently representing their ideas multimodally. This study concludes with implications for how educators can learn from listening to emergent bilingual students' perspectives when integrating technology in the classroom. Abstract :